2007
DOI: 10.1017/s0954422407842235
|View full text |Cite
|
Sign up to set email alerts
|

Macular zeaxanthins and lutein – a review of dietary sources and bioavailability and some relationships with macular pigment optical density and age-related macular disease

Abstract: The retina is unique in the human body in containing three xanthophyll carotenoids; 3R,3 0 Rzeaxanthin, meso-zeaxanthin (MZ) and lutein. Humans consume 1 to 3 mg lutein per d and the lutein:zeaxanthin ratio in the diet is about 5:1.Xanthophyll pigments occur widely in vegetables and fruits but MZ is found in only a few foods such as the shrimp carapace and fish skin. In spite of the amounts of the different xanthophylls in the diet, zeaxanthin and MZ occur in approximately equal amounts in the eye, and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 69 publications
(183 reference statements)
2
56
0
1
Order By: Relevance
“…However, it should be noted that the supplement used in the study by Thurnham et al was suspended in oil; whereas, our study used a micro-encapsulated form of the supplement suspended in starch, which may account for, at least in part, the low serum response reported here, given that oil has been shown to promote carotenoid absorption. 53 The investigation by Thurnham et al (2008) reported an average increase of 0.209 ± 0.128 μmol/L in serum concentrations of MZ (following supplementation with 8 mg per day of this carotenoid over a 22-day study period). 27 Similarly, the study by Bone et al observed augmented average serum concentrations of MZ (0.094 ± 0.071 μmol/L) following supplementation with 14 mg per day of this carotenoid over a 120-day period.…”
Section: 51mentioning
confidence: 97%
See 1 more Smart Citation
“…However, it should be noted that the supplement used in the study by Thurnham et al was suspended in oil; whereas, our study used a micro-encapsulated form of the supplement suspended in starch, which may account for, at least in part, the low serum response reported here, given that oil has been shown to promote carotenoid absorption. 53 The investigation by Thurnham et al (2008) reported an average increase of 0.209 ± 0.128 μmol/L in serum concentrations of MZ (following supplementation with 8 mg per day of this carotenoid over a 22-day study period). 27 Similarly, the study by Bone et al observed augmented average serum concentrations of MZ (0.094 ± 0.071 μmol/L) following supplementation with 14 mg per day of this carotenoid over a 120-day period.…”
Section: 51mentioning
confidence: 97%
“…This observation is important, given that the amount of MZ in human donor eyes has been reported as ∼7.7 ng and also given that an active binding protein for Z and MZ have been identified in retinal tissue. [53][54][55] There has only been one other study to date that has measured MPOD following daily supplementation with MZ. That study, recently performed by Bone et al, in 2007, included 10 normal subjects, who were supplemented with 14.9 mg of MZ, 5.5 mg of L, and 1.4 mg of Z, for 120 days.…”
Section: 51mentioning
confidence: 99%
“…Lutein and zeaxanthin carotenoids cannot be synthesized in vivo and therefore must be obtained from the diet. Egg yolks have been reported as an important dietary source of lutein and zeaxanthin, and a range of studies have been conducted to analyze these nutrients in egg yolks, including commercial egg yolks (Goodrow et al, 2006;Olson, Ward, & Koutsos, 2008;Schlatterer & Breithaupt, 2006;Thurnham, 2007). However, under processing conditions, the highly reactive, electron-rich carotenoid molecule present in egg yolks suffers oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…L and Z are entirely of dietary origin, whereas MZ is thought to derive (at least in part) from retinal L through a poorly understood bioconversion process (Bone et al, 1993), although its presence in the diet has not been comprehensively studied, and remains under investigation (Thurnham, 2007). MP is a powerful antioxidant (Khachik et al, 1997) and thus has a putative neuroprotective function in the retina.…”
mentioning
confidence: 99%